Verorten - verhandeln - verkörpern : interdisziplinäre Analysen zu Raum und Geschlecht - Förschler, Silke; Habermas, Rebekka; Rossbach, Nikola (Dynamiken von Raum und Geschlecht ;, 2014)
Especially under the aspect of globalization, the mutual influence of space and gender moves increasingly into the view of cultural studies and the social sciences. This volume brings together interdisciplinary contributions that analyze the constructed character of space and gender terms, which is constitutive of social, cultural, and political worlds on the one hand and imaginary, fictional worlds on the other hand. The epoch-spanning and interdisciplinary studies provide a contribution both to contemporary debates on the spatial turn as well as to current positions in gender studies.